STRATEGIC SOLUTIONS FOR ENGLISH STUDENTS: ENHANCING EMPLOYABILITY THROUGH BETTER CURRICULUM ALIGNMENT - Waqar Mahmood Khan; Zubia Shakeel; Dr. Rabia Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
There is a significant misalignment between the curricula of Pakistani universities and the demands of the local job market. This issue seems particularly obvious for English undergraduate students who, despite having completed a 4-year BS program, struggle to either pass competitive exams for earning jobs or qualify M.Phil. and Ph.D. entrance exams to secure admissions. These exams often include analytical reasoning and mathematics, which seem irrelevant to students’ degree in linguistics and literature. This misalignment indicates a broader systemic issue where educational content is not in conjunction with students' fields of study or market demands. This study using a quantitative methodology, collected data from BS English graduates and employers through a standardized questionnaire and identified the gaps between university curricula and demands of the job market. It further emphasizes the mismatch in assessment criteria and curriculum content, focusing on fields such as semantics, pragmatics, phonetics, critical discourse analysis, and literary studies, including novels, criticism, and poetry. The study draws on Human Capital Theory and Curriculum Theory. Human Capital Theory considers education as a critical investment required to develop a skilled workforce. Curriculum Theory emphasizes the designing of a curriculum that is relevant to societal needs, ensuring comprehensiveness and connectedness. The existing disconnect suggests an inadequate utilization of human capital, leaving students unprepared for their careers. To bridge this gap, Pakistan’s Higher Education Commission (HEC) should re-align curricula and assessment methods with relevant fields of study. Applying Constructive Alignment Theory, which concurs learning objectives, teaching methods, and evolutions, could better equip students with the necessary competencies. Addressing this gap is important to retaining talent in our country and preparing our students for successful careers.